Quantitative finance - James, Jessica, 1968-; Institute of Physics (Great Britain) (Bristol [England] (Temple Circus, Temple Way, Bristol BS1 6HG, UK) : IOP Publishing, 2017)
Quantitative finance is a field that has risen to prominence over the last few decades. It encompasses the complex models and calculations that value financial contracts, particularly those which reference events in the future, and apply probabilities to these events. While adding greatly to the flexibility of the market available to corporations and investors, it has also been blamed for worsening the impact of financial crises. But what exactly does quantitative finance encompass, and where did these ideas and models originate? We show that the mathematics behind finance and behind games of chance have tracked each other closely over the centuries and that many well-known physicists and mathematicians have contributed to the field.
Introduction -- Background -- Current directions -- Outlook.
"Version: 20170101"--Title page verso.
Includes bibliographical references (pages 16-17).
Final-year undergraduates, new PhD students and early-career scientists.
Also available in print.
System requirements: Adobe Acrobat Reader, EPUB reader. or Kindle reader.
Mode of access: World Wide Web.
Keywords: MATHEMATICS / Applied; Finance -- Mathematical models; Applied mathematics